THE INFLUENCE OF SOCIAL MEDIA PROMOTION FEATURES AND STRATEGIES TO INCREASE BRAND AWARENESS IN LINE APPLICATIONS - Yunus Indra Purnama; Nur Wening (ZILLZELL MEDIA PRIMA, 2023)
The problem discussed in this study is the influence of features and promotional strategies on brand awareness at PT. Line in 2023. The purpose of this study is to determine the influence of features and promotional strategies on brand awareness at PT. Line. The population used in this study is students of management study program and accounting study program at Yogyakarta University of Technology who use the LINE application. The determination of the sample in this study used the slovin formula of 80 respondents. Data collection method using questionnaire/questionnaire. The data that has been collected is then processed with data processing techniques, namely by conducting validity and reliability tests. Data analysis techniques used are Normality Test, Heteroscedastic Test and Multicollinearity Test. The hypothesis tests used are simple linear regression tests, t-tests, significance tests, determination coefficient tests, multiple linear regression tests and simultaneous tests. The result of the research obtained is that each brand may have a combination of different features depending on the industry, target market, and business goals. In this case, it is important to develop a brand awareness strategy that is in accordance with the characteristics and values of the brand. By combining various elements in a promotional strategy, a brand can achieve a higher level of brand awareness among the target market of the business undertaken, so it is important to continuously monitor and evaluate the effectiveness of the promotion strategy to identify the necessary changes. And simultaneously in research it was found that it is important to strike the right balance between superior product features and appropriate promotional strategies. The synergy between the two can create a strong experience for consumers and strengthen the brand's position in the company's mind.